PEMBELAJARAN TEATER TUNGGAL (MONOLOG) DALAM KEGIATAN EKSTRAKURIKULER DI SMK NEGERI 1 BULANGO SELATAN MENGGUNAKAN METODE “ROLE PLAYING” - Alifah Aulia Shabrina Jusuf; La Ode Karlan; Mimy Astuty Pulukadang; Riana Diah Sitharesmi; Trubus Semiaji (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to explore the Implementation of Monologue Learning in Extracurricular activities as an effort to overcome lost learning, experienced by students due to the COVID-19 pandemic. Lost learning is a condition in which students lose the opportunity to learn optimally due to disruptions in the face-to-face learning process that occurs during the pandemic. Bold learning implemented during the pandemic is often unable to accommodate the differentiated needs of students, especially at SMK Negeri 1 Bulango Selatan School. Because of this, researchers are interested in conducting research at the school. This study uses the Role Playing method, because this method is Flexible, and can encourage students to be more active through role simulations that are close to Real Situations. This study uses a qualitative approach, the data in this study were collected through observation, documentation, interviews and assessment instruments. The population in this study were students in grades X, XI, XII who actively participated in the Theater Extracurricular. The sample of this study was 15 people, divided into 3 Participants and 12 as observers. The results of the study were; from 3 participants, they had performed quite varied performances. And 12 students as observers, 8 people observed carefully and 4 people were not serious and needed to be improved.